ENHANCING STUDENTS' READING ABILITY THROUGH PEER-ASSISTED LEARNING STRATEGIES (PALS) - Hasnani Hasnani; Agus Ismail (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2020)
Abstract:This study aims to enhance the students' reading ability through Peer-Assisted Learning Strategies (PALS) in SMA Negeri 19 Makassar. This research is a Classroom Action Research (CAR), which consists of four stages: planning, implementing, observing, and reflecting. The research techniques used are pretest, post-test, and observation. The findings showed that the use of Peer-Assisted Learning Strategies was successful in improving the students' reading ability. The improvement can be seen from the mean score of the students in cycle one is 23.1, which is categorized as good, while in cycle two, it is 73.1, which is classified as very good. Seventeen students met the Minimum Completeness Criteria (MCC) in cycle one, and 22 students completed the MCC in cycle two. Therefore, this research concludes that Peer-Assisted Learning strategies improve the students' learning outcomes of reading ability in SMA Negeri 19 Makassar.Abstrak:Penelitian ini bertujuan untuk meningkatkan kemampuan membaca siswa melalui Peer-Assisted Learning Strategies (PALS) di SMA Negeri 19 Makassar. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) yang terdiri dari 4 tahap; perencanaan, pelaksanaan, observasi, dan refleksi. Teknik penelitian ini menggunakan tes dan wawancara. Hasil penelitian menunjukkan bahwa penggunaan Peer-Assisted Learning Strategies berhasil meningkatkan kemampuan membaca siswa SMA Negarei 19 Makassar. Peningkatan tersebut terlihat dari nilai rata-rata siswa pada siklus I sebesar 23,1 dengan kategori baik, dan pada siklus II sebesar 73,1 tergolong sangat baik. Tujuh belas siswa memenuhi Kriteria Ketuntasan Minimum (KKM) pada siklus satu, dan 22 siswa memenuhi KKM pada siklus dua. Oleh karena itu, penelitian ini menyimpulkan bahwa kemampuan membaca siswa meningkat melalui model pembelajaran Peer-Assisted Learning Strategies di SMA Negarei 19 Makassar.